Numeracy Skills Disorders: Review of Causes and Neuropsychological Mechanisms of Dyscalculia - Glinik O.A (Moscow State University of Psychology and Education, 2022)
The article presents a review of foreign studies on the numerical difficulties and numerical disorders. The main modern theories of the mechanisms underlying the difficulties and disorders of counting are reflected, various classifications of dyscalculia are compared, and the neuropsychological foundations of the brain organization of counting are analyzed according to foreign scientists. It is noted that in the world of psychological science, the issues of the causes and mechanisms of difficulties and disorders of counting are still insufficiently developed, and the results of empirical researches are contradictory. It is concluded that for further study of dyscalculia it is necessary to analyze the psychological structure of counting and its changes under the influence of learning, taking into account the structural and functional features of the brain organization of quantitative information processing.